Evidencing Anthropology. 115th Annual Meeting of the American Anthropological Association, 16–20 November, 2016. Minneapolis, MN. USA - Sokolova, Elena (Journal of Economic Sociology, 2017)
The Annual Meeting of the American Anthropological Association is one of the biggest international events in anthropology. Judging by the association’s website, the event offers 750 sessions and includes more than 6,000 participants from all over the world. It is supported by key professional societies, such as the Society for Cultural Anthropology, as well as by numerous special interest groups, sections, and committees. This article review covers the thematic aspects of the conference; the program’s features, including the scale of the meeting and a focus on anthropologic careers; the attitude of the professional community towards an anthropologist’s role in society and shifts in this attitude; changing aspects of ethnographic methods; and finally some additional observations made by the author during the 115th Annual Meeting of the American Anthropological Association entitled “Evidence. Accident. Discovery,” held in Minneapolis in November 2016. Attention is paid to educational programs within the community of anthropologists, the practical importance of informal communication at the conference, and the further exploration of public media tools—mainly digital—such as social networks and blogs. The next Annual Meeting, “Anthropology Matters!” will further promote the active social participation of anthropologists and proceed with “anthropological investigation, translation, influence and action.” This conference matters: it is a great opportunity to stay informed on the actual directions that anthropology and its methodology are taking and it is also a helpful tool to collect diverse professional feedback on anthropological research projects.